Deliberative Decision-Making in Macaques Removes Reward-Driven Response Vigor - Daddaoua, Nabil; Jedema, Hank P.; Bradberry, Charles W. (Frontiers in Behavioral Neuroscience, 2021)
Most of our daily decisions are governed by one of two systems: an impulsive system driving instantaneous decisions and a deliberative system driving thoughtful ones. The impulsive system reacts to immediately available concrete rewards. In contrast, the deliberative system reacts to more delayed rewards and/or punishments, which imposes consideration of longer term choice consequences. Contingency management for addiction treatment is hypothesized to engage deliberative processes. Ultimately, in both decision-making situations, an action is needed to enact the decision. Whether those actions differ in implementation is an open question whose answer could inform as to whether distinct neural systems are engaged. To address this, we trained monkeys to perform a decision-making task where they made a choice on a touch screen between two visual cues predicting different amounts of reward. In immediate choice (IC) trials, the cues appeared at the final response locations where subjects could immediately touch the chosen cue. In deliberated choice (DC) trials, cues appeared orthogonally to the response locations. After a delay, allowing for decision formation, the cues were displaced to the randomly assigned response locations permitting subjects to reach for the chosen cue. Both trial types showed an effect of cue value on cue selection time. However, only IC trials showed an effect of the competing cue on response vigor (measured by movement duration), and reach trajectories that deviated in the direction of the competing cue, suggesting a decision reexamination process. Reward modulation of response vigor implicates dopaminergic mechanisms. In DC trials, reach trajectories revealed a commitment to the chosen choice target and the reach vigor was not modulated by the value of the competing cue. Our results suggest that choice-action dynamics are shaped by competing offers only during instantaneous, impulsive choice. After a deliberated decision, choice-action dynamics are unaffected by the alternative offer cue, demonstrating a commitment to the choice. The potential relevance to contingency management is discussed.